Moscow Treaty of the USSR-Germany and «Letter on German Unity». From Conflict to Compromise - A. M. Filitov (Vestnik MGIMO-Universiteta)
The article considers the course and results of the Soviet-West German negotiations that led to the conclusion of the Moscow Treaty of August 12, 1970, which became an important factor in defusing international tensions on the European continent. Special attention is paid to the problem of the genesis of the so-called "Letter on German unity", the adoption of which the Soviet side stubbornly insisted on the representatives of Germany. The article reveals the flexible tactics of the Soviet delegation, which was headed by the Minister of foreign Affairs of the USSR AA. Gromyko: taking into account, in particular, the position of the GDR, the diplomats opposed the inclusion in the text of the Treaty of any provisions relating to the unification of Germany, but left open the prospect of such unification in the future. Some realism and willingness to compromise showed and West German negotiators, among whom special credit belongs to the personal emissary of Chancellor Brandt E. Bahr. On the basis of these compromises, a common position of the parties on the conclusion and subsequent ratification of the Moscow Treaty was worked out. The article pays due attention to the "US factor" in Soviet-West German relations. Formally declaring a positive attitude to the" new Eastern policy " of Germany, in fact the American side tried to compromise it in every possible way and complicate the process of preparing the Moscow Treaty. There is also some inconsistency in the German diplomacy in departing from previous political dogmas, primarily from the claims to the sole representation of all Germans. The main conclusion of the article is that as a result of the complex and sometimes conflicting Soviet-West German negotiation process, its participants managed to overcome the real contradiction between the principle of inviolability of borders and the right to national self-determination. In the current international situation, when this contradiction is artificially aggravated by the supporters of confrontation, the experience gained in the development and coordination of the provisions of the Moscow Treaty is of actual practical importance. The work is written on the basis of previously not entered into scientific circulation of primary sources from the Archive of foreign policy of the Russian Federation, as well as published West German documents.The author declares absence of conflict of interests.